A graphene hybrid composite material and its application in conductive materials
By using hybrid technology of porous network graphene and epoxy resin in epoxy resin conductive materials, a porous network structure is formed, which solves the problems of low thermal conductivity of epoxy resin conductive materials and easy agglomeration of graphene, and improves high conductivity, thermal conductivity and compression performance, extends the life of electronic components.
Patent Information
- Application Number
- CN202310051091.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-02
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-02-02
AI Technical Summary
Due to the low thermal conductivity of existing epoxy resins in electronic components, the operating temperature of electronic components is too high, the stability is reduced, and the life of the electronic components is shortened. Graphene is prone to agglomeration in epoxy resin, resulting in poor conductivity and thermal conductivity.
The porous network graphene is hybridized with epoxy resin, and the porous network structure is formed by combining polyterephthalyl terephthalyl phenylenediamine and graphene oxide. The porous network thermal and electrical structure supported by carbon fiber is formed by freeze-drying and carbonization.
The conductivity and thermal conductivity of conductive materials are improved, the compression performance is enhanced, the performance degradation caused by graphene agglomeration is avoided, the working temperature of electronic components is effectively reduced, and its stability and life are improved.
Smart Images

Figure CN115948026B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphene conductive materials, and in particular to a graphene hybrid composite material and application thereof in conductive materials. Background Art
[0002] Due to the rapid development of miniaturization and micro-miniaturization of electronic components and high density and high integration of printed circuit boards, conductive materials are used to make pastes to achieve high line resolution and effectively improve production efficiency. Conductive pastes are generally adhesives with certain conductive properties after curing or drying. They usually have base resins and conductive fillers, i.e. conductive particles, as the main components. The conductive particles are combined together through the bonding effect of the base resin to form a conductive path, thereby achieving conductive connection of the bonded materials.
[0003] The high degree of cross-linking between epoxy resin molecules gives it super-high hardness, strength, heat resistance, solvent resistance and chemical stability, and it is widely used in the conductive materials of electronic components. However, with the integration and modularization of electronic components, the heat accumulation of electronic equipment during operation has increased exponentially, causing the operating temperature of electronic components to be too high. Epoxy resin is essentially a poor conductor of electricity and heat, and its thermal conductivity is very low.
[0004] Conductive materials generate a lot of heat when electronic components are running. For every 2°C rise in the temperature of electronic components, the stability of electronic components decreases by 10%. The heat accumulation directly damages the life of electronic components and can lead to serious consequences, such as fire and other serious accidents. Therefore, in order to ensure the stable and reliable operation of electronic components, it is necessary to find ways to reduce the operating temperature. Rapid and timely heat dissipation in electronic components has become an important research topic in modern integrated electronic packaging. The development of high-performance epoxy conductive materials has become an urgent need for the development of the current industry.
[0005] The single-layer atomic structure of graphene has super-high hardness and strength, and its excellent thermal and electrical conductivity make the function of epoxy resin qualitatively improved. Due to the high specific surface area and cost of graphene, a very low filling amount can significantly improve the physical and mechanical properties of epoxy resin. In order to make epoxy resin obtain the excellent performance of graphene materials, it is necessary to overcome the agglomeration of graphene in epoxy resin. Agglomerated graphene not only leads to poor electrical and thermal conductivity, but also easily causes defective structures in epoxy resin, resulting in a significant deterioration in the compression performance of epoxy resin conductive materials. Summary of the invention
[0006] Based on the technical problems existing in the background technology, the present invention proposes a graphene hybrid composite material and its application in conductive materials.
[0007] The invention provides a graphene hybrid composite material, comprising porous network graphene and epoxy resin infused in the porous network graphene and cured; wherein the porous network graphene is prepared by combining poly(p-phenylene terephthalamide) with a graphene sheet to form a porous network, which is then processed by freeze drying and carbonization.
[0008] A method for preparing the graphene hybrid composite material comprises the following steps:
[0009] S1. Add 30-40 parts of bisphenol A epoxy resin, 2-6 parts of polyacrylamide, 12-20 parts of filler and 0.1-1 parts of color powder into a high-speed mixer and stir for 10-60 minutes at a stirring speed of 200-500 r / min and a stirring temperature of 40-50° C., cool to room temperature, reduce the stirring speed to 50-150 r / min, add 1-5 parts of aromatic amine curing agent, 1-2 parts of accelerator and 1-3 parts of diluent, continue stirring for 10-20 minutes, and vacuum degassing to obtain an epoxy resin system;
[0010] The accelerator includes accelerator DyhardUR 500 and 3-mercaptopropionate;
[0011] S2, adding 1-5 parts of graphene oxide and 1-3 parts of poly(p-phenylene terephthalamide) to 20-50 parts of water and stirring evenly, adding 2-6 parts of hydrogen iodide, stirring at room temperature for 1-2h, the stirring speed is 1000-2000r / min, sealing, standing at 70-80℃ for 10-20h, soaking in water for 1-3 days, wherein the water is changed every 2-5h, freeze-drying, carbonizing in a nitrogen atmosphere for 10-30min, the carbonization temperature is 800-1000℃, and cooling to room temperature to obtain porous network graphene;
[0012] S3, adding the porous network graphene into a container, injecting the epoxy resin system therein by vacuum filtration, curing at room temperature, and trimming to obtain the graphene hybrid composite material.
[0013] Preferably, in S1, in the accelerator, the mass ratio of accelerator DyhardUR 500 to 3-mercaptopropionic acid ester is 10:1-5.
[0014] Preferably, in S1, the aromatic amine curing agent is a mixture of m-phenylenediamine and diaminodiphenylmethane.
[0015] Preferably, in S1, in the aromatic amine curing agent, the mass ratio of m-phenylenediamine to diaminodiphenylmethane is 1-2:1.
[0016] Preferably, in S1, the diluent is at least one of butyl glycidyl ether, 2-ethyl-hexyl glycidyl ether, diethylene glycol diglycidyl ether and ethylene glycol diglycidyl ether.
[0017] Preferably, in S1, the filler is at least one of white carbon black, aluminum hydroxide and calcium carbonate.
[0018] An application of the graphene hybrid composite material as described above in conductive materials.
[0019] The technical effects of the present invention are as follows:
[0020] In the present invention, bisphenol A epoxy resin and polyacrylamide have good mutual solubility, wherein polyacrylamide can reduce the room temperature viscosity of the compounded resin, and bisphenol A epoxy resin can enhance the stability of the system. The two are compounded, and Dyhard UR 500 accelerator is used to promote the conversion of the thiol group in 3-mercaptopropionate into thiol ions, which then react with the aromatic amine curing agent to promote the epoxy group in the bisphenol A epoxy resin to combine, and the system can be cured at room temperature;
[0021] Graphene oxide and poly(p-phenylene terephthalamide) are dispersed in water. Poly(p-phenylene terephthalamide) and graphene oxide are mutually expanded and dispersed evenly in the aqueous solution. Then, the oxygen-containing functional groups of graphene oxide are removed by strong reduction with hydrogen iodide, and the water solubility is reduced. The steric hindrance formed by poly(p-phenylene terephthalamide) bonded to the graphene sheet through hydrogen bonds restricts the aggregation of graphene, and promotes the formation of a porous network structure of graphene. Then, after freeze drying and carbonization treatment in a nitrogen atmosphere, poly(p-phenylene terephthalamide) is pyrolyzed to form carbon fibers and plays a bridging role between graphene sheets.
[0022] The epoxy resin system is further infused into the porous network graphene by vacuum filtration and cured at room temperature to obtain a porous network thermal and electrical conductive structure supported by carbon fibers and graphene sheets. The epoxy resin system fully penetrates into the porous network structure and, after being cured at room temperature, forms an integral structure with extremely high bonding strength. This not only solves the problem of poor dispersion and easy agglomeration when directly adding graphene, but the porous network also hinders the movement of epoxy resin molecular chains, hinders the generation and expansion of microcracks, and effectively enhances the compression performance of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a comparison chart of the electrical conductivity and thermal conductivity of the products of Example 5 of the present invention and Comparative Examples 1-4.
[0024] Figure 2 This is a comparison chart of the compression performance of the products of Example 5 of the present invention and Comparative Example 2. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is described in detail below through specific embodiments.
[0026] Example 1
[0027] A graphene hybrid composite material comprises porous network graphene and epoxy resin infused in the porous network graphene and cured; wherein the porous network graphene is prepared by combining poly(p-phenylene terephthalamide) with a graphene sheet to form a porous network, which is then processed by freeze drying and carbonization.
[0028] A method for preparing a graphene hybrid composite material comprises the following steps:
[0029] S1, add 30kg bisphenol A epoxy resin, 2kg polyacrylamide, 12kg calcium carbonate, 0.1kg color powder into a high-speed stirrer and stir for 10min, the stirring speed is 200r / min, the stirring temperature is 40°C, cool to room temperature, reduce the stirring speed to 50r / min, add 1kg aromatic amine curing agent, 1kg accelerator, 1kg diethylene glycol diglycidyl ether, continue stirring for 10min, and vacuum degassing to obtain an epoxy resin system;
[0030] The accelerator is composed of accelerator Dyhard UR 500 and 3-mercaptopropionic acid ester in a mass ratio of 10:1; the aromatic amine curing agent is composed of a mixture of meta-phenylenediamine and diaminodiphenylmethane in a mass ratio of 1:1.
[0031] S2, adding 1kg of graphene oxide and 1kg of poly(p-phenylene terephthalamide) to 20kg of water and stirring evenly, adding 2kg of hydrogen iodide, stirring at room temperature for 1h, the stirring speed is 1000r / min, sealing, standing at 70℃ for 10h, soaking in water for 1 day, changing water every 2h, freeze-drying, carbonizing in nitrogen atmosphere for 10min, the carbonization temperature is 800℃, and cooling to room temperature to obtain porous network graphene;
[0032] S3, adding the porous network graphene into a container, injecting the epoxy resin system therein by vacuum filtration, curing at room temperature, and trimming to obtain the graphene hybrid composite material.
[0033] Example 2
[0034] A graphene hybrid composite material, comprising porous network graphene, and epoxy resin infused into the porous network graphene and cured;
[0035] The porous network graphene is prepared by combining poly(p-phenylene terephthalamide) with a graphene sheet to form a porous network, which is then freeze-dried and carbonized in sequence.
[0036] A method for preparing a graphene hybrid composite material comprises the following steps:
[0037] S1, add 40kg bisphenol A epoxy resin, 6kg polyacrylamide, 20kg calcium carbonate, 1kg color powder into a high-speed stirrer and stir for 60min at a stirring speed of 500r / min and a stirring temperature of 50°C, cool to room temperature, reduce the stirring speed to 150r / min, add 5kg aromatic amine curing agent, 2kg accelerator, 3kg diethylene glycol diglycidyl ether, continue stirring for 20min, and vacuum degassing to obtain an epoxy resin system;
[0038] The accelerator is composed of accelerator Dyhard UR 500 and 3-mercaptopropionic acid ester in a mass ratio of 10:5; the aromatic amine curing agent is composed of a mixture of meta-phenylenediamine and diaminodiphenylmethane in a mass ratio of 2:1.
[0039] S2, 5kg of graphene oxide and 3kg of poly(p-phenylene terephthalamide) were added to 50kg of water and stirred evenly, 6kg of hydrogen iodide was added, stirred at room temperature for 2h, the stirring speed was 2000r / min, sealed, stood at 80℃ for 20h, soaked in water for 3 days, wherein the water was changed every 5h, freeze-dried, carbonized in nitrogen atmosphere for 30min, the carbonization temperature was 1000℃, and cooled to room temperature to obtain porous network graphene;
[0040] S3, adding the porous network graphene into a container, injecting the epoxy resin system therein by vacuum filtration, curing at room temperature, and trimming to obtain the graphene hybrid composite material.
[0041] Example 3
[0042] A graphene hybrid composite material, comprising porous network graphene, and epoxy resin infused into the porous network graphene and cured;
[0043] The porous network graphene is prepared by combining poly(p-phenylene terephthalamide) with a graphene sheet to form a porous network, which is then freeze-dried and carbonized in sequence.
[0044] A method for preparing a graphene hybrid composite material comprises the following steps:
[0045] S1, add 32kg bisphenol A epoxy resin, 3kg polyacrylamide, 13kg white carbon black, 0.2kg color powder into a high-speed mixer and stir for 20min, the stirring speed is 250r / min, the stirring temperature is 42°C, cool to room temperature, reduce the stirring speed to 70r / min, add 2kg aromatic amine curing agent, 1.2kg accelerator, 1.2kg ethylene glycol diglycidyl ether, continue stirring for 12min, and vacuum degassing to obtain an epoxy resin system;
[0046] The accelerator is composed of accelerator Dyhard UR 500 and 3-mercaptopropionic acid ester in a mass ratio of 10:2; the aromatic amine curing agent is composed of a mixture of meta-phenylenediamine and diaminodiphenylmethane in a mass ratio of 1.8:1.
[0047] S2, 2kg of graphene oxide and 1.2kg of poly(p-phenylene terephthalamide) were added to 25kg of water and stirred evenly, 3kg of hydrogen iodide was added, stirred at room temperature for 1.2h, the stirring speed was 1200r / min, sealed, allowed to stand at 72°C for 12h, soaked in water for 1.5 days, wherein the water was changed every 2.5h, freeze-dried, carbonized in a nitrogen atmosphere for 12min, the carbonization temperature was 820°C, and cooled to room temperature to obtain porous network graphene;
[0048] S3, adding the porous network graphene into a container, injecting the epoxy resin system therein by vacuum filtration, curing at room temperature, and trimming to obtain the graphene hybrid composite material.
[0049] Example 4
[0050] A graphene hybrid composite material, comprising porous network graphene, and epoxy resin infused into the porous network graphene and cured;
[0051] The porous network graphene is prepared by combining poly(p-phenylene terephthalamide) with a graphene sheet to form a porous network, which is then freeze-dried and carbonized in sequence.
[0052] A method for preparing a graphene hybrid composite material comprises the following steps:
[0053] S1, 36kg bisphenol A epoxy resin, 5kg polyacrylamide, 18kg aluminum hydroxide, 0.8kg color powder were added into a high-speed mixer and stirred for 50min at a stirring speed of 380r / min and a stirring temperature of 46°C, cooled to room temperature, and the stirring speed was reduced to 120r / min, 4kg aromatic amine curing agent, 1.5kg accelerator, and 1.5kg butyl glycidyl ether were added, and stirring was continued for 18min, and vacuum degassing was performed to obtain an epoxy resin system;
[0054] The accelerator is composed of accelerator Dyhard UR 500 and 3-mercaptopropionic acid ester in a mass ratio of 10:4; the aromatic amine curing agent is composed of a mixture of meta-phenylenediamine and diaminodiphenylmethane in a mass ratio of 1.2:1.
[0055] S2, 2kg of graphene oxide and 3.2kg of poly(p-phenylene terephthalamide) were added to 45kg of water and stirred evenly, 3kg of hydrogen iodide was added, stirred at room temperature for 1.5h, the stirring speed was 1200r / min, sealed, allowed to stand at 75°C for 12h, soaked in water for 1.5 days, wherein the water was changed every 3h, freeze-dried, carbonized in a nitrogen atmosphere for 25min, the carbonization temperature was 950°C, and cooled to room temperature to obtain porous network graphene;
[0056] S3, adding the porous network graphene into a container, injecting the epoxy resin system therein by vacuum filtration, curing at room temperature, and trimming to obtain the graphene hybrid composite material.
[0057] Example 5
[0058] A graphene hybrid composite material, comprising porous network graphene, and epoxy resin infused into the porous network graphene and cured;
[0059] The porous network graphene is prepared by combining poly(p-phenylene terephthalamide) with a graphene sheet to form a porous network, which is then freeze-dried and carbonized in sequence.
[0060] A method for preparing a graphene hybrid composite material comprises the following steps:
[0061] S1, 36kg bisphenol A epoxy resin, 4kg polyacrylamide, 15kg calcium carbonate, 0.5kg color powder were added to a high-speed stirrer and stirred for 40min at a stirring speed of 300r / min and a stirring temperature of 46°C, cooled to room temperature, and the stirring speed was reduced to 120r / min, 3kg aromatic amine curing agent, 1.5kg accelerator, and 2kg 2-ethyl-hexyl glycidyl ether were added, and stirring was continued for 15min, and vacuum degassing was performed to obtain an epoxy resin system;
[0062] The accelerator is composed of accelerator Dyhard UR 500 and 3-mercaptopropionic acid ester in a mass ratio of 10:3. The aromatic amine curing agent is a mixture of metaphenylenediamine and diaminodiphenylmethane, and the mass ratio of metaphenylenediamine to diaminodiphenylmethane is 1.5:1.
[0063] S2, 3kg of graphene oxide and 2kg of poly(p-phenylene terephthalamide) were added to 30kg of water and stirred evenly, 4kg of hydrogen iodide was added, stirred at room temperature for 1.5h, the stirring speed was 1500r / min, sealed, and allowed to stand at 75°C for 15h, and then soaked in water for 2 days, wherein the water was changed every 4h, freeze-dried, and carbonized in a nitrogen atmosphere for 25min at a carbonization temperature of 900°C, and then cooled to room temperature to obtain porous network graphene;
[0064] S3, adding the porous network graphene into a container, injecting the epoxy resin system therein by vacuum filtration, curing at room temperature, and trimming to obtain the graphene hybrid composite material.
[0065] Comparative Example 1
[0066] A method for preparing a graphene hybrid composite material comprises the following steps:
[0067] S1, 36kg bisphenol A epoxy resin, 4kg polyacrylamide, 15kg calcium carbonate, 0.5kg color powder were added into a high-speed mixer and stirred for 40min at a stirring speed of 300r / min and a stirring temperature of 46°C, cooled to room temperature, and the stirring speed was reduced to 120r / min, 3kg dicyandiamide, 1.5kg accelerator, and 2kg 2-ethyl-hexyl glycidyl ether were added, and stirring was continued for 15min, and vacuum degassing was performed to obtain an epoxy resin system;
[0068] The accelerator is composed of accelerator Dyhard UR 500 and 3-mercaptopropionic acid ester in a mass ratio of 10:3.
[0069] S2, 3kg of graphene oxide and 2kg of poly(p-phenylene terephthalamide) were added to 30kg of water and stirred evenly, 4kg of hydrogen iodide was added, stirred at room temperature for 1.5h, the stirring speed was 1500r / min, sealed, and allowed to stand at 75°C for 15h, and then soaked in water for 2 days, wherein the water was changed every 4h, freeze-dried, and carbonized in a nitrogen atmosphere for 25min at a carbonization temperature of 900°C, and then cooled to room temperature to obtain porous network graphene;
[0070] S3, adding the porous network graphene into a container, injecting the epoxy resin system therein by vacuum filtration, curing at room temperature, and trimming to obtain the graphene hybrid composite material.
[0071] Comparative Example 2
[0072] A method for preparing a graphene hybrid composite material comprises the following steps:
[0073] 36 kg of bisphenol A epoxy resin, 4 kg of polyacrylamide, 15 kg of calcium carbonate and 0.5 kg of color powder were added into a high-speed mixer and stirred for 40 min at a stirring speed of 300 r / min and a stirring temperature of 46°C. After cooling to room temperature, the stirring speed was reduced to 120 r / min, 3 kg of aromatic amine curing agent, 1.5 kg of accelerator and 2 kg of 2-ethyl-hexyl glycidyl ether were added, stirring was continued for 15 min, vacuum degassing was performed, curing was performed at room temperature, and trimming was performed to obtain a graphene hybrid composite material.
[0074] The accelerator is composed of accelerator Dyhard UR 500 and 3-mercaptopropionic acid ester in a mass ratio of 10:3. The aromatic amine curing agent is a mixture of metaphenylenediamine and diaminodiphenylmethane, and the mass ratio of metaphenylenediamine to diaminodiphenylmethane is 1.5:1.
[0075] Comparative Example 3
[0076] A method for preparing a graphene hybrid composite material comprises the following steps:
[0077] 36 kg of bisphenol A epoxy resin, 4 kg of polyacrylamide, 15 kg of calcium carbonate, 3 kg of nano-graphene and 0.5 kg of color powder were added into a high-speed mixer and stirred for 40 min at a stirring speed of 300 r / min and a stirring temperature of 46°C. After cooling to room temperature, the stirring speed was reduced to 120 r / min, 3 kg of aromatic amine curing agent, 1.5 kg of accelerator and 2 kg of 2-ethyl-hexyl glycidyl ether were added, stirring was continued for 15 min, vacuum degassing was performed, curing was performed at room temperature, and trimming was performed to obtain a graphene hybrid composite material.
[0078] The accelerator is composed of accelerator Dyhard UR 500 and 3-mercaptopropionic acid ester in a mass ratio of 10:3. The aromatic amine curing agent is a mixture of metaphenylenediamine and diaminodiphenylmethane, and the mass ratio of metaphenylenediamine to diaminodiphenylmethane is 1.5:1.
[0079] Comparative Example 4
[0080] A method for preparing a graphene hybrid composite material comprises the following steps:
[0081] S1, 36kg bisphenol A epoxy resin, 4kg polyacrylamide, 15kg calcium carbonate, 0.5kg color powder were added to a high-speed stirrer and stirred for 40min at a stirring speed of 300r / min and a stirring temperature of 46°C, cooled to room temperature, and the stirring speed was reduced to 120r / min, 3kg aromatic amine curing agent, 1.5kg accelerator, and 2kg 2-ethyl-hexyl glycidyl ether were added, and stirring was continued for 15min, and vacuum degassing was performed to obtain an epoxy resin system;
[0082] The accelerator is composed of accelerator Dyhard UR 500 and 3-mercaptopropionic acid ester in a mass ratio of 10:3. The aromatic amine curing agent is a mixture of metaphenylenediamine and diaminodiphenylmethane, and the mass ratio of metaphenylenediamine to diaminodiphenylmethane is 1.5:1.
[0083] S2, add 3kg of graphene oxide and 2kg of poly(p-phenylene terephthalamide) to 30kg of water and stir evenly, add 4kg of hydrogen iodide, stir at room temperature for 1.5h, the stirring speed is 1500r / min, seal, stand at 75℃ for 15h, soak in water for 2 days, change the water every 4h, freeze-dry, and cool to room temperature to obtain porous network graphene;
[0084] S3, adding the porous network graphene into a container, injecting the epoxy resin system therein by vacuum filtration, curing at room temperature, and trimming to obtain the graphene hybrid composite material.
[0085] Performance Testing
[0086] 1. Electrical conductivity and thermal conductivity test
[0087] The conductivity of the products of Example 5 and Comparative Examples 1-3 was tested using a Tech RST-8 four-probe resistivity tester. The thermal conductivity of the products of Example 5 and Comparative Examples 1-4 was tested using a PPMS-9T physical property testing system produced by QUANTUM DESIGN, USA; Testing principle: a heat pulse is applied to the surface of one side of the product, and the heat is transferred to the other side of the surface. The system collects the temperature difference in the sample and calculates the thermal conductivity of the material based on the geometric shape of the sample.
[0088] The product size is 3mm×5mm×5mm, and the test temperature is 25℃. The test results are as follows Figure 1 shown.
[0089] Depend on Figure 1 It can be seen that compared with Comparative Example 2, the conductivity of Comparative Example 3 is only improved by adding nanographene, which is only about 0.23S / m. This is because the nanographene sheets are very easy to agglomerate and cannot form an effective connection. The conductivity of Example 5 can be improved by 10 2 S / m or more, this is because the interconnected conductive network structure in Example 5 is filled in the epoxy resin, which improves the electron transmission capacity of the system. Comparative Example 1 cannot be cured at room temperature, and the electrical conductivity and thermal conductivity are measured by the method.
[0090] The thermal conductivity improvement rate of Example 5 is the highest, reaching more than 0.7W / mK, while the high-temperature carbonization process is not performed in Comparative Example 4, and its thermal conductivity improvement is very low. This is because the nanographene after chemical reduction has many defects and cannot effectively form a thermal conductive network in the epoxy resin. After high-temperature carbonization, the thermal conductivity of Example 5 is more than 3 times higher than that of the pure epoxy resin in Comparative Example 2, and more than 2 times higher than that of Comparative Example 4. This is because high-temperature carbonization repairs the defective structure of graphene, the lattice size increases, and the carbon fiber forms an effective lap structure thereon, resulting in excellent thermal conductivity in Example 5.
[0091] 2. Compression performance test
[0092] The compression performance test of the products of Example 5 and Comparative Example 2 was carried out using an INSTRON 1185 universal material testing machine. The products were cylindrical, with 5 samples in each group. The test was carried out according to the soft foam compression strength standard. The compression rate was 50 mm / min. The static compression stress-strain curve of the test material was as follows: Figure 2 shown.
[0093] Depend on Figure 2 It can be seen that in Example 5, the epoxy resin system is vacuum filtered and infused into the porous network graphene. The epoxy resin system fully penetrates into the porous network structure. After curing at room temperature, they form an integral body with extremely high bonding strength. The porous network hinders the movement of the epoxy resin molecular chains, hinders the generation and expansion of microcracks, and effectively enhances the compression performance of the product.
[0094] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A graphene hybrid composite material, characterized in that: It includes porous network graphene, and epoxy resin infused in the porous network graphene and cured; The porous network graphene is prepared by combining poly(p-phenylene terephthalamide) with a graphene sheet to form a porous network, and then undergoing freeze drying and carbonization treatment in sequence. The specific operation is as follows: S1. Stir bisphenol A epoxy resin, polyacrylamide, filler and color powder for 10-60 minutes at a stirring temperature of 40-50° C., cool to room temperature, add aromatic amine curing agent, accelerator and diluent, and continue stirring for 10-20 minutes, and vacuum degassing to obtain an epoxy resin system; The accelerators include: accelerator Dyhard UR 500 and 3-mercaptopropionate; S2, adding graphene oxide and poly(p-phenylene terephthalamide) into water and stirring evenly, adding hydrogen iodide and stirring at room temperature for 1-2 hours, sealing, standing at 70-80°C for 10-20 hours, soaking in water for 1-3 days, wherein the water is changed every 2-5 hours, freeze-drying, carbonizing in a nitrogen atmosphere for 10-30 minutes, the carbonization temperature is 800-1000°C, and cooling to room temperature to obtain porous network graphene; S3, adding the porous network graphene into a container, pouring the epoxy resin system into the container by vacuum filtration, curing at room temperature, and trimming to obtain a graphene hybrid composite material; The mass ratio of bisphenol A epoxy resin, polyacrylamide, filler, color powder, aromatic amine curing agent, accelerator, diluent, graphene oxide, poly(p-phenylene terephthalamide) and hydrogen iodide is 30-40:2-6:12-20:0.1-1:1-5:1-2:1-3:1-5:1-3:2-6.
2. The graphene hybrid composite material according to claim 1, characterized in that: In S1, the mass ratio of accelerator Dyhard UR500 to 3-mercaptopropionic acid ester is 10:1-5.
3. The graphene hybrid composite material according to claim 1, characterized in that: In S1, the aromatic amine curing agent is a mixture of m-phenylenediamine and diaminodiphenylmethane.
4. The graphene hybrid composite material according to claim 3, characterized in that: In S1, in the aromatic amine curing agent, the mass ratio of m-phenylenediamine to diaminodiphenylmethane is 1-2:
1.
5. The graphene hybrid composite material according to claim 1, characterized in that: In S1, the diluent is at least one of butyl glycidyl ether, 2-ethyl-hexyl glycidyl ether, diethylene glycol diglycidyl ether and ethylene glycol diglycidyl ether.
6. The graphene hybrid composite material according to claim 1, characterized in that: In S1, the filler is at least one of white carbon black, aluminum hydroxide and calcium carbonate.
7. An application of the graphene hybrid composite material as claimed in claim 1 in conductive materials.
Citation Information
Patent Citations
Graphene aerogel and hybrid composite material thereof as well as preparation method and application of graphene aerogel
CN106422995A
Preparation process of low-thermal-expansion composite material
CN113372107A